Religious minorities in Christian, Jewish and Muslim law (5th-15th centuries) - Berend, Nora; Hameau-Masset, Youna 1985-; Nemo-Pekelman, Capucine 1973-; Tolan, John Victor 1959- (Religion and law in medieval Christian and Muslim societies, 2017)
The fruit of a sustained and close collaboration between historians, linguists and jurists working on the Christian, Muslim and Jewish societies of the Middle Ages, this book explores the theme of religious coexistence (and the problems it poses) from a resolutely comparative perspective. The authors concentrate on a key aspect of this coexistence: the legal status attributed to Jews and Muslims in Christendom and to dhimmis in Islamic lands.